2008
DOI: 10.1093/carcin/bgn159
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tyrosine phosphorylation of membrane type 1-matrix metalloproteinase reduces tumor cell proliferation in three-dimensional matrices and abrogates tumor growth in mice

Abstract: Pericellular proteolysis of the extracellular matrix by membrane type 1-matrix metalloproteinase (MT1-MMP) confers tumor cells with the ability to proliferate within three-dimensional (3D) matrices and sustains tumor growth in mice. In this study, we show that in addition to its matrix-degrading activity, phosphorylation of MT1-MMP on its unique tyrosine residue located within its cytoplasmic sequence (Tyr573) may also participate to these processes. Fibrosarcoma cells expressing a proteolytically active but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
1
41
1
Order By: Relevance
“…MT1-MMP is cited as the key MMP that regulates ECM degradation at invadopodia (Poincloux et al, 2009) and Src kinase activity is known to regulate phosphorylation of MT1-MMP and proteins associated with its trafficking to the cell membrane (Nyalendo et al, 2008;Nyalendo et al, 2007). Future studies should address whether WT Src is necessary to control trafficking to, or activation of MT1-MMP at invadopodia.…”
Section: Discussionmentioning
confidence: 99%
“…MT1-MMP is cited as the key MMP that regulates ECM degradation at invadopodia (Poincloux et al, 2009) and Src kinase activity is known to regulate phosphorylation of MT1-MMP and proteins associated with its trafficking to the cell membrane (Nyalendo et al, 2008;Nyalendo et al, 2007). Future studies should address whether WT Src is necessary to control trafficking to, or activation of MT1-MMP at invadopodia.…”
Section: Discussionmentioning
confidence: 99%
“…Small interfering RNA and mismatch siRNA were synthesized by Qiagen and annealed to form duplexes. MSCs were transiently transfected with cDNA constructs encoding full-length MT1-MMP (15) or a nonphosphorylatable MT1-MMP mutant Y573F (17).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently reported that MT1-MMP can be phosphorylated on a tyrosine residue (Tyr573) of the cytoplasmic domain in a manner that is dependent on Src tyrosine kinase, and that this phosphorylation is required for tumour-cell proliferation and invasion of 3D collagen matrices and for tumour growth in nude mice (Nyalendo et al, 2008;Nyalendo et al, 2007). As noted above, the LLY573 sequence is required for clathrin-mediated uptake of MT1-MMP (Uekita et al, 2001), suggesting a possible regulation of endocytosis by phosphorylation downstream of Src.…”
Section: Clathrin-mediated Endocytosis Of Mt1-mmpmentioning
confidence: 99%